Gender analysis of the World Health Organization online learning program on Immunization Agenda 2030 - Nyasulu, Boetumelo Julianne; Heidari, Shirin; Manna, Michela; Bahl, Jhilmil; Goodman, Tracey (Frontiers in Global Women's Health, 2023)
Vaccine-preventable diseases pose a significant threat to children under five globally, creating disparities in immunization coverage. Despite its cost-effectiveness and life-saving potential, immunization faces challenges in achieving equitable coverage. Gender inequalities deeply influence access to healthcare, affecting immunization rates. This study examines the action plans submitted by participants of the World Health Organization's (WHO) IA2030 Scholar Level 1 certification course in 2021. A qualitative analysis was conducted on a subset of 111 action plans that scored above 75%, employing narrative thematic analysis to categorize and explore gender incorporation and identified barriers based on the IA2030 Gender Guide. Among the 111 analyzed action plans, gender considerations were present in almost all plans, underscoring the effectiveness of integrating gender perspectives in the course curriculum. The most frequently cited barriers included low education and health literacy, issues related to accessing quality immunization services, gendered dynamics in decision-making within households, and limited access to resources and mobility, predominantly impacting women. The findings confirm that gender inequalities significantly contribute to suboptimal immunization coverage. An intersectional approach, recognizing diverse social markers impacting immunization, is vital to address disparities effectively. Moreover, the need for gender-sensitive data and deeper understanding of intersectional dynamics was emphasized. The study highlights the importance of gender-transformative interventions, including community engagement and efforts targeting both men and women to enhance immunization coverage. While acknowledging limitations, such as potential biases in peer evaluations and the need for wider inclusivity in gender perspectives, this analysis underscores the significance of mainstreaming gender in immunization capacity-building programs. The integration of gender considerations not only raises awareness but also equips professionals to create more gender-responsive immunization programs. Continuous efforts to incorporate gender perspectives can lead to more effective, equitable, and gender-transformative immunization initiatives at various levels.